ONOMATOPE DALAM KOMIK ONLINE ONE PUNCH MAN VOL 1-3 KARYA ONE DITINJAU DARI SUDUT PANDANG FONOLOGI - Siti Rohmatun; Arza Aibonotika; Nana Rahayu (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract: This study aims to describe the types, forms and meanings of giseigoand giongo in the comic Online One Punch Man Vol 1-3 Karya One according to thephonological point of view using the theory of onomatope forms (Akimoto, 2002)phonological theory (Tsujimura, 1996) and the theory of vowel and consonant meaning(Hamano, 1986). This research is a qualitative descriptive research. The source of thisresearch data is Online Comics One punch man. The results of this study show that stopvoiceless sounds coming from the velar are characterized by the consonant /k/ whilestop voiced sound coming from the velar and heavy sounds are characterized with theconsonant /g/, retained sounds are characterized by small tsu, nasal voiced sounds arecharacterized by the consonant /n/, vibrating sounds from the palatal are marked withthe consonant /r/ and continuous sounds are characterized by repetition.Key Words: Onomatope, giseigo, giongo, phonology.